Introducing a two temperature plasma ignition in inertial confined targets under the effect of relativistic shock waves: The case of DT and pB11. (10th July 2015) - Eliezer, Shalom; Henis, Zohar; Nissim, Noaz; Pinhasi, Shirly Vinikman; Martinez Val, José Maria
Abstract A criterion for a two temperature plasma nuclear fusion ignition is derived by using a common model. In particular, deuterium-tritium (DT) and proton–boron11 (pB11) are considered for pre-compressed plasma. The ignition criterion is described by a surface in the three-dimensional space defined by the electron and ion temperatures Te, Ti, and the plasma density times the hot spot dimension, ρ·R. The appropriate fusion ion temperatures Ti are larger than 10 keV for DT and 150 keV for pB11. The required value of ρ·R for pB11 ignition is larger by a factor of 50 or more than for DT, depending on the electron temperature. Furthermore, our ignition criterion obtained here for pB11 fusion is practically impossible for equal electron and ion temperatures. In this paper it is suggested to use a two temperature laser induced shock wave in the intermediate domain between relativistic and non-relativistic shock waves. The laser parameters required for fast ignition are calculated. In particular, we find that for DT case one needs a 3 kJ/1 ps laser to ignite a pre-compressed target at about 600 g/cm3. For pB11 ignition it is necessary to use more than three orders of magnitude of laser energy for the same laser pulse duration.